2001
DOI: 10.1053/ajcd.2001.22777
|View full text |Cite
|
Sign up to set email alerts
|

Dental metal allergy in patients with oral, cutaneous, and genital lichenoid reactions

Abstract: Sensitization to dental metals is more common among LP and LL patients than in routinely tested patients, and might be an etiologic or triggering factor in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…[1][2][3][18][19][20][21] These studies underscore the importance of metal sensitivity, particularly in patients with oral lichenoid lesions. In our group, 7 of the 10 allergens with the highest percentage of positive reactions were metals.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[1][2][3][18][19][20][21] These studies underscore the importance of metal sensitivity, particularly in patients with oral lichenoid lesions. In our group, 7 of the 10 allergens with the highest percentage of positive reactions were metals.…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies have addressed the effects of metal allergies in patients with dental restorations or orthodontic devices. [1][2][3][4][5][6][7][8][9][10][11] However, few studies have used larger oral allergen screening series that, in addition to metals, included flavorings, preservatives, and dental acrylates. [12][13][14][15][16] We report the results of patch tests to the 85 allergens in our oral screening series.…”
mentioning
confidence: 99%
“…However, allergen reaction to mercury is not limited to OLP. Cutaneous and genital lichenoid reactions also feature positive patch test reactions [25,58].…”
Section: Oral Lichen Planus and Oral Lichenoid Lesionsmentioning
confidence: 99%
“…There is a body of research on the clinical results of OLP patients following dental amalgam removal and its association with patch testing [14,17,[20][21][22][23][24][25]. A systematic review of 14 cohort and five case-controlled trials of patients with OLP demonstrated that after dental amalgam replacement, between 35 and 100 % of patients had complete disease resolution.…”
Section: Oral Lichen Planus and Oral Lichenoid Lesionsmentioning
confidence: 99%
“…Metals are thought to cause various types of allergic reactions (including dermatitis, lichen planus, palmoplantar pustulosis, asthma, and rhinitis) [1][2][3][4][5][6], and even to cause carcinomas [4]. Although allergic mechanisms are known to be implicated in these diseases, the mechanism underlying metal allergy is obscure.…”
Section: Introductionmentioning
confidence: 99%